2021
DOI: 10.3390/membranes11090674
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of ABCA1 Gene Expression in Smoking and Chronic Obstructive Pulmonary Disease

Abstract: Smoking is a key modifiable risk factor for developing the chronic obstructive pulmonary disease (COPD). When smoking, many processes, including the reverse transport of cholesterol mediated by the ATP binding cassette transporter A1 (ABCA1) protein are disrupted in the lungs. Changes in the cholesterol content in the lipid rafts of plasma membranes can modulate the function of transmembrane proteins localized in them. It is believed that this mechanism participates in increasing the inflammation in COPD. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…These changes intensified with age and were accompanied by disruption of alveolar architecture and epithelialization of the remaining alveoli as a result of hyperplasia of type II pneumocytes [ 174 ]. These studies showed decreased expression of ABCA1 in lung tissues in smoking and COPD patients [ 175 ].…”
Section: Anti-inflammatory Function Of Hdlmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes intensified with age and were accompanied by disruption of alveolar architecture and epithelialization of the remaining alveoli as a result of hyperplasia of type II pneumocytes [ 174 ]. These studies showed decreased expression of ABCA1 in lung tissues in smoking and COPD patients [ 175 ].…”
Section: Anti-inflammatory Function Of Hdlmentioning
confidence: 99%
“…Importantly, smoking impairs reverse cholesterol transport mediated by ABCA1 and ABCG1 [ 175 , 204 , 205 ]. This may lead to an increase in the number of macrophages overloaded with cholesterol, which contributes to their inflammatory activation [ 36 , 136 ].…”
Section: Anti-inflammatory Function Of Hdlmentioning
confidence: 99%
“…Thus, members of the ABCA subfamily play a significant role in the mechanisms of innate immunity mediated by lipid transport, which is of great clinical importance [78,79].…”
Section: The Abca Subfamilymentioning
confidence: 99%
“…Studies in recent years have convincingly demonstrated the involvement of lipids in inflammation. Smoking has been shown to disrupt the normal processes that maintain lipid homeostasis in the lungs, which may be part of the pathogenesis of COPD [ 7 ]. It should be noted that cigarette smoke contributes to an oxidant/antioxidant imbalance due to exogenous reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%